Cultural Values as a Basis for Well-Being: the Logic of The Relationship and Importance of the Institute of Expert Examination Interpretation; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 7 : Lifelong Wellbeing in the World (WELLSO 2015) - Royzen E. A. (2016, 2016)
Title screen